(untitled) (Research, Society and Development, 2022)
COVID-19 caused a global pandemic and afflicted the lives of many individuals, in a period when physical contact represented a great risk to human life, so measures were taken to prevent the spread of the virus and protect people. As a result, labor relations suffered a great impact and had to be adapted quickly to the new scenario, being necessary the adoption of the practice of working from home. Therefore, an investigation over the work from home in the pandemic and the impacts that Brazilian workers suffered through the adoption of this type of labor relations has become elementary to understand whether it is an ally or a villain for workers. In order to obtain the exposed conclusions, a bibliographic review was used based on works, scientific articles and the Brazilian legislation, that are relevant to the proposed theme. In this way, it was concluded that despite having been an alternative measure to avoid a crisis and reduce the risk of contagion of the disease, working from home can become a great ally of the labour market. however, some points should be analysed and improved, such as the need for more specific legislation on the regulation of this type of labour relation, as well as the technological and structural preparation for the performance of labour activities.